Team spirit? [videorecording] (Brazil : Mind Resources, 2005)
Learning objectives : To enable people to see themselves as part of the team, not just as individuals. About the training video : People who have their own job to do often fail to see themselves as part of a team. Team spirit? is a light-hearted, but high-impact way of showing them the importance of teamwork. Its engaging, humorous, and realistic format examines the examples of three diverse people whose failure to appreciate this need has disastrous effects on their colleagues and customers. One individual does not understand how her administration job fits in with others, and because she fails to provide them with information, they cannot do their jobs properly and customers become dissatisfied. A mechanic is good at his job but fails to communicate and accept responsibility. This affects the service his garage provides, until he learns how to adopt a proactive attitude, helping workmates and taking the initiative. Colleagues in a tourist information centre have very different working styles: one is studious and meticulous, while the other is dynamic and full of ideas. They learn that they can achieve much more by co-operating and sharing skills, benefitting from greater motivation at the same time. This programme is ideal for anyone working in a team, those involved in customer care, and in new-starter training programmes. Learning chapters : An introduction to team spirit --- Not checking what's expected of you --- Checking what's expected of you --- Not clarifying your role --- If in doubt clarify --- Clarifying your role --- Lacking initiative and avoiding responsibility --- Taking the initiative and accepting responsibility --- Not supporting colleagues --- Supporting colleagues --- Valuing different skills in colleagues --- Sharing information and communicating --- Summary. Source : Video arts webpage.